Pengaruh E-Commerce dan Kualitas Produk terhadap Keputusan Pembelian melalui Kepuasan Konsumen sebagai Variabel Intervening - Riki Fitriana; Umar Chadhiq (AKSES: Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of E-Commerce and Product Quality on Purchase Decisions Through Consumer Satisfaction as an Intervening Variable Amid the Covid-19 Pandemic (Case Study of Umkm Kebab Mecca Jln. Cipinang Muara I, East Jakarta). The sample used in this study was 100 consumers. The data analysis technique used the Partial Least Square (PLS) approach with the help of the SmartPLS 3.0 program. The results of this study indicate that e-commerce on purchasing decisions has a positive and insignificant effect. Product quality on purchasing decisions has a positive and significant effect. E-commerce on consumer satisfaction has a positive and significant effect. Product quality on consumer satisfaction has no effect. Consumer satisfaction on purchasing decisions has a positive and significant effect. Consumer satisfaction does not interfere with e-commerce on purchasing decisions and consumer satisfaction does not intervene in product quality on purchasing decisions. Keywords: E-commerce, Product Quality, Consumer Satisfaction, Purchase Decision